Play School favourite bedtime stories - Australian Broadcasting Corporation (Sydney, NSW : ABC Books, 1996)
This classic collection of Play School stories is the perfect book to share with young children at bedtime. The delightful short stories and familiar Play School images will enchant and calm little ones, leaving them ready for a good night's sleep. Ages: 0-3.
For pre-school age.
Keywords: Bedtime -- Pictorial works -- Juvenile fiction; Bedtime -- Juvenile fiction; Children's stories; Picture books; Australian fiction